Experimental and simulation investigation of porous Functionally Graded beam under bending loading - Fayyadh, Muthanna Ismaeel; Qwam Alden, Arz (Anbar Journal of Engineering Sciences, 2023)
In recent decades, functionally graded porous structures have been utilized due to their light weight and excellent energy absorption. They have various applications in the aerospace, biomedical, and engineering fields. Therefore, the balance between material strength and light weight is the goal of the researchers to decrease the cost. Samples of PLA material were designed and manufactured using a 3D printer according to international standard specifications to study the effect of porosity gradient through thickness. An experimental three-point bending test was performed, and then simulations were performed using ANSYS 2022 R1 software on samples with functionally gradient different porosity layers to verify the experimental results. The results from the experiment and the numerical values were in excellent alignment with an error rate of no more than 13%. The maximum bending load and maximum deflection of the beam were specified experimentally and compared with the numerical solution. The maximum bending and the maximum deflection When the porosity layer in the middle of the beam, matched the ideal maximum bending load (190,194) N experimentally and numerically, respectively. The maximum deflection (5.9,6.4) mm experimentally and numerically, respectively was obtained in samples with varying porous layers.